Integrated assistance to the village community of Nagori Tiga Ras to create an independent and sustainable ecotourism area in Pardamean village, Simalungun regency - Sitohang, Ance Marintan D; Situmorang, Sawitania Christiany (Talenta Publisher, 2020)
Indonesia is a country that has natural resources that are very potential, especially in the tourism sector. One of them is in the Lake Toba area, which is located in the province of North Sumatra. Among the various existing villages, Nagori Tigaras Village, which is directly adjacent to the south and west of Lake Toba, is a village that has all the potential that is no less attractive to be developed into an independent and sustainable tourism area. However, this potential is not supported by the availability of qualified and qualified human resources to manage all of this potential so that assistance is needed that does not only last for a moment but is sustainable so that the village can manage its territory independently to produce sustainable efforts to support national economic growth. Based on these considerations, this community service activity was carried out which began with socialization activities in the form of Focus Group Discussions (FGD) which were followed by participatory mapping together with the community and local government. From this activity, produced a documentary film, a dedication journal, and news that has been published in print media which functions as a media for promotion and communication.